A STUDY OF FUNGAL INFECTIONS IN CLINICALLY SUSPECTED TUBERCULOSIS PATIENTS - G, AMAR KUMAR; J, VISALASREE (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The purpose of the current study is to create awareness among the clinicians on the role of fungal etiological agents in suspected tuberculosis (TB) cases. This would help in preventing unnecessary use of anti-tubercular drugs and in decreasing drug-resistant TB cases. Methods: Prospective study was performed in the clinical microbiology laboratory of Annapoorana Medical College and Hospital, Salem, Tamil Nadu, from January 2013 to February 2017 subsequently getting approval from the institutional ethics committee. 464 sputum samples were collected from both inpatients and outpatients of numerous departments. Signs and symptoms of clinically suspected TB patients were noted for all cases. Statistical Analysis: Categorical variables were summarized by percentages (%). The Fishers exact test (2 × 2) analysis was done. Results: A total of 119 fungal isolates were isolated from the culture. The highest number of fungal isolates were of Candida species (n=61) (30.5%) followed by Cryptococcus neoformans n=38 (19%) and Histoplasma capsulatum n=20 (10%). Amongst the used anti-fungals, Fluconazole was the most effective drug for all the isolated fungi followed by Itraconazole, Amphotericin B, Voriconazole, and Nystatin. Conclusion: Our study findings indicate the significance of considering fungal infections as a prospect however treating disseminated granulomatous infections, even in immune-competent cases, particularly if the reaction to the TB therapy is insufficient.